Review of Tree Species in Dry Dipterocarp Forest, Savannakhet Province, Lao PDR - KHAMMANIVONG, Khanxay; THAMMAVONG, Viengsamone; KHOTPATHOOM, Thananh; WANNENG, Phongxiong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The aim of this research was to estimate the relationship between tree density and elevation of tree species in Dry Dipterocarp Forest. Methods applying for this study used ground verified plot inventory from Phaipalath et.al (2018) to regenerated analysis 6 sites, data analysis applied several techniues of statistics, such as descriptive analyisis and linear regression. The results found that there were 6 species and 3 genuses that are significant dominance in Dry Dipterocarp Forest site in Laos. The largest species is Shorea sp, it is highest density contributing in everywhere of elevation levels from 124 to 218 m. Relationship between density and elevation of tree numbers increased based on different sea levels showed significantly at R2=0.57, Dipterocarpus obtusifolius decreased in low elevation significantly at R2=0.63, Shorea siamensis increased significantly at R2=0.74, in high elevation. The tree species of Xylia xylocarpa, Cratoxylum formosum and Vatica odorata were low significantly correlation with the sea elevation at R2<0.5.